Input requirements and their costs for fodder banks and other livestock services - Suleiman, H.; Magaji, D. (International Livestock Centre for Africa, 1984)
Presents input requirements and costs for fodder banks and other services. Includes materials for establishing fodder bank fence and for feeding, and management inputs by pastoralists & extension.